Integration of Character Education in Aqidah Akhlaq Learning for Fourth Grade Students at Madrasah Diniyah Baabussalam, Kemukten Village - Casudi Casudi; Haris Diar Rizki; Siti Winda Normasari; Prada Laila Isyrina; Elza Roikhatul Miskiyyah (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
Education serves not only to cultivate intellectual capacity but also to shape the character of the younger generation—instilling noble morals, honesty, discipline, responsibility, and social awareness. In the face of increasingly complex contemporary challenges—such as globalization, the digital revolution, and an emerging instant culture—education is required to provide students with a strong foundation of character. Within this context, character education emerges as an urgent necessity to address various social, moral, and spiritual issues in society. Based on the research problem outlined, this study aims to examine the process of integrating character education into the Aqidah Akhlaq learning of fourth-grade students at Madrasah Diniyah Baabussalam, Kemukten Village. The findings reveal that the integration of character education into Aqidah Akhlaq instruction contributes to the improvement of students’ moral conduct, ethics, and overall character development. This is reflected in their increased enthusiasm during learning activities, particularly when the instructional method involves exemplary storytelling. The integration specifically incorporates six core character values: religiosity, discipline, hard work, creativity, independence, and democratic behavior.